PRIMARY AND SECONDARY NOMINATION IN THE SEMANTICS OF ORNITHONYMS - Yigitaliyeva Muhlisa Ahadovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is devoted the content and system of the linguistic image and the portable meaning of the ornitonymous word with comparative analysis.